Information literacy : essential skills for the information age - Eisenberg, Michael; Lowe, Carrie A.; Spitzer, Kathleen L. (Westport, CT : Libraries Unlimited, 2004)
Traces the history of information literacy, discussing its economic importance, examining past, present, and current research in the field, and exploring how information literacy relates to the national standards transforming K-12 education and higher education.
Spitzer's name appears first on the earlier edition.
Includes bibliographical references (p. 289-382) and index.
Booklist.
Library Media Connection starred.
Reference and Research Book News.
Professional
Keywords: Education -- Aims and objectives -- United States; Education -- Standards -- United States; Information literacy; Information literacy -- Study and teaching (Elementary) -- United States; Information literacy -- Study and teaching (Secondary) -- United States; Information literacy -- Study and teaching -- United States; Education -- United States -- Aims and objectives; Education -- United States -- Standards; Information literacy; Information literacy -- Study and teaching; Information science -- United States